Plasma Tuning Local Environment of Hexagonal Boron Nitride for Oxidative Dehydrogenation of Propane - Liu, Zhankai; Yan, Bing; Meng, Shengyan; Liu, Rui; Lu, Wen‐Duo; Sheng, Jian; Yi, Yanhui; Lu, An‐Hui (Angewandte Chemie International Edition, 2021)
Hexagonal boron nitride (h‐BN) has lately received great attention in the oxidative dehydrogenation (ODH) reaction of propane to propylene for its extraordinary olefin selectivity in contrast to metal oxides. However, high crystallinity of commercial h‐BN and elusive cognition of active sites hindered the enhancement of utilization efficiency. Herein, four kinds of plasmas (N2, O2, H2, Ar) were accordingly employed to regulate the local chemical environment of h‐BN. N2‐treated BN exhibited a remarkable activity, i.e., 26.0 % propane conversion with 89.4 % selectivity toward olefins at 520 °C. Spectroscopy demonstrated that “three‐boron center” N‐defects in the catalyst played a pivotal role in facilitating the conversion of propane. While the sintering effect of the “BOx” species in O2‐treated BN, led to the suppressed catalytic performance (12.4 % conversion at 520 °C). Plasma (N2, O2, H2, Ar) regulated h‐BN with distinct local environment were obtained and employed for ODH of propane: N2 treated BN containing more three‐boron center nitrogen‐defects exhibited remarkable propane conversion of 26.0 % with olefin selectivity of 89.4 % at 520 °C. O2 treated BN showed deactivation due to the sintering effect of “BOx”. N‐H and B‐H generated during H2 treatment, may be unable to facilitate the reaction activity.